UMP launch Malaysia’s first Academic Initiative on Campus - UMP, PNC
Universiti Malaysia Pahang (UMP) strengthened its partnership with IBM and HeiTech Padu Berhad with the launch of Malaysia’s first Academic Initiative on Campus “Center of Excellence” on 9 March 2011 recently.